THE TEACHING AND LEARNING PRACTICE PERFORMED BY PRE-SCHOOL TEACHERS DURING COVID 19 OUTBREAK - Sri Fatmaning Hartatik; Anis Na’il Fulka Bia’yuni (UIBU, 2020)
Covid 19 outbreak have made all sectors to switch their performance from face to face interaction to virtual ones; from massive gathering and meetings to social distancing. This is also applied in education sector. This study was intended to describe how teaching and learning process took place during the Covid 19 outbreak. This study focused on the teaching and learning process in pre-school level as the researchers wondered how teachers facilitated learning for young learners. From the interview, the researchers noticed that all teachers used WhatsApp to get themselves connected to their students. In addition, they also send the student work book to their students’ houses. Next, two teachers needed to teach some students in the classroom as learning from home did not work for few students, the numbers of the students and the meetings of course were limited. The findings of this studies were expected to give insights to stake holders, policy makers, education experts, and scientist to help teachers and learners at pre-school level so that they still can achieve the teaching and learning objectives during the Covid 19 outbreak